Ways Of Development Of Small Business Enterprises In The Republic Of Uzbekistan - Abdulxakimov Zuhrali Tursunalievich; Ergashev Jamshid Jamoliddinovich; Abdul Rahmat (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
This article examines the activities of small businesses in the Republic of Uzbekistan and the profound structural changes during the pandemic and their impact on the economy.